2000
DOI: 10.1165/ajrcmb.23.2.3975
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Origins of Human Intrapulmonary Arteries

Abstract: Recent studies on the morphogenesis of the pulmonary arteries have focused on nonhuman species such as the chick and the mouse. Using immunohistochemical techniques, we have studied 16 lungs from human embryos and fetuses from 28 d of gestation to newborn, using serial sections stained with a panel of antibodies specific for endothelium, smooth muscle, and extracellular matrix proteins. Cell replication was also assessed. Serial reconstruction showed a continuity of circulation between the heart and the capill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
97
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 38 publications
6
97
1
2
Order By: Relevance
“…The prevalence of vasculogenesis over angiogenesis in five to seven weeks embryos is also supported by our findings regarding the coexpression of CD34 and Ki67; our data showed that there were no proliferating endothelial cells in five weeks embryos, and in seven weeks embryos, proliferation of endothelial cells was inconstant. Our results support also the fact that lung arteries are formed by vasculogenesis while pulmonary capillaries are formed by angiogenesis (Hall et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of vasculogenesis over angiogenesis in five to seven weeks embryos is also supported by our findings regarding the coexpression of CD34 and Ki67; our data showed that there were no proliferating endothelial cells in five weeks embryos, and in seven weeks embryos, proliferation of endothelial cells was inconstant. Our results support also the fact that lung arteries are formed by vasculogenesis while pulmonary capillaries are formed by angiogenesis (Hall et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…2 and 3). Another possibility is that there are two alternative sources of smooth muscle, the mesothelium and the splanchnic mesoderm-derived mesenchyme (3,(20)(21)(22). More detailed lineage tracing studies and analysis of the phenotypes of labeled and unlabeled cells in the walls of the blood vessels will be needed to distinguish between these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…During the embryonic and pseudoglandular phase of development (< 18 weeks' gestation), all airways to the level of the terminal bronchiole form by division. Around each terminal bud, capillaries develop and form the pulmonary circulation 14 . Thus the pattern of pulmonary arteries and veins depends on the airway branching.…”
Section: Discussionmentioning
confidence: 99%